2006
DOI: 10.1002/pip.673
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency µc-Si solar cells made by very high-frequency plasma-enhanced chemical vapor deposition

Abstract: Microcrystalline silicon‐based single‐junction p–i–n solar cells have been fabricated by very high‐frequency plasma enhanced chemical vapor deposition using a showerhead cathode at high pressures and under silane depletion conditions. The i‐layers are made near the transition from amorphous to crystalline. It was found that, especially at high crystalline fractions, the open‐circuit voltage and fill factor are very sensitive to the morphology of the substrate. At an i‐layer deposition rate 0·45 nm/s, we have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 16 publications
0
37
0
2
Order By: Relevance
“…In PECVD, R H is decreased during i-layer deposition [15] to suppress the development of the deposited nc-Si:H i-layers toward higher crystallinity. Using this technique, a general increase in all the cell parameters was observed, thus improving the solar cell efficiency considerably [15,16]. In our case, since the i-layer structure develops in the opposite direction, we used a reverse H 2 profiling scheme, namely an increase of the R H while depositing the i-layer, instead of decreasing it.…”
Section: Solar Cell With Reverse H 2 Profilingmentioning
confidence: 99%
“…In PECVD, R H is decreased during i-layer deposition [15] to suppress the development of the deposited nc-Si:H i-layers toward higher crystallinity. Using this technique, a general increase in all the cell parameters was observed, thus improving the solar cell efficiency considerably [15,16]. In our case, since the i-layer structure develops in the opposite direction, we used a reverse H 2 profiling scheme, namely an increase of the R H while depositing the i-layer, instead of decreasing it.…”
Section: Solar Cell With Reverse H 2 Profilingmentioning
confidence: 99%
“…At constant hydrogen dilution, due to conical growth of grain columns, there is a quadratic increase of the crystallinity with an increase of thickness. By employing a parabolic type of grading where the hydrogen dilution is reduced step wise to maintain the crystallinity at a constant level, a more homogeneous growth of the i-layer can be made, as confirmed by comparing the Raman spectra obtained from the top (n) and bottom (p) side of the nanocrystalline silicon cell [29]. The efficiencies of the p-i-n nc-Si solar cells with and without parabolic grading are shown in Fig.…”
Section: Structural Evolutionmentioning
confidence: 87%
“…It has been observed that the crystalline component is a major deciding factor for the photosensitivity of the material. The best cell performance is obtained at R c of ∼0.4 [29]. Therefore, this quantity is meticulously maintained in the material when comparing the behaviour of solar cells with i-layers made at different deposition conditions.…”
Section: Transition Type Materialsmentioning
confidence: 99%
“…[7][8][9][10][11] However, in 2002 a best-cell V oc of 580 mV was reported for c-Si: H solar cells prepared by hot wire deposition. 12 For very high frequency ͑VHF͒ plasma-deposited solar cells a best-cell V oc around 570 mV was reported in 2005 by the application of a hot wire ͑HW͒ deposited buffer layer between the p and i layers.…”
mentioning
confidence: 99%